Academic building energy conservation opportunities - Manegdeg, Ferdinand G. (Philippine Engineering Journal)
A framework for determining academic building energy consumption was developed, energy audits on selected academic buildings at the University of the Philippines Diliman were conducted, the different influencing factors to electricity consumption were identified, and energy policy options to ensure effective energy management in the next 5 years are suggested. The electricity consumption is primarily due to air-conditioning and lighting loads or data processing. The energy intensity for lecture rooms, conference rooms, libraries, administration offices and auditoriums were established. Policies for future and existing buildings were formulated. It is recommended that a thorough profiling of student usage and technical usage of laboratories be conducted.